The role of international production sharing in EU productivity and competitiveness - Carlo Altomonte; Gianmarco I. P. Ottaviano (EIB Papers, 2011)
Is international production sharing associated with stronger competitiveness? We address this question from the complementary viewpoints of firms and industries. We show that international production sharing is indeed associated with stronger competitiveness not only at the firm level but also at the industry level. From the viewpoint of firms, stronger competitiveness gives access to a larger number of more complex options when it comes to the design of international operations. From the viewpoint of industries, stronger competitiveness arises from the possibility of reallocating resources from less to more productive firms. For both firms and industries stronger competitiveness arises from the possibility of exploiting a richer set of internationalization strategies to deal with the challenges and the opportunities of globalization.
Keywords: 330; Internationale Arbeitsteilung; Internationaler Wettbewerb; Standortwahl; Produktivität; EU-Staaten